How Does Comprehensive Income Affect Earnings Management In The Financial Sector? - Pratama, Sari Indra; Ratmono, Dwi (Integrated Journal of Business and Economics (IJBE), 2025)
This study seeks to evaluate the impact of disclosing comprehensive income, including net income and other comprehensive income, on financial sector companies listed on the Indonesia Stock Exchange from 2019 to 2023. This research uses a quantitative descriptive approach with panel data regression analysis through SmartPLS on 62 samples selected using purposive sampling technique. The analytical results indicate that net income does not influence earnings management within the banking sector listed on the Indonesian Stock Exchange; in this context, net income as a predictor of earnings management appears to be constrained to certain circumstances.  Conversely, other comprehensive income substantially influences earnings management within the financial industry listed on the Indonesian Stock Exchange. Enhancing the openness of Other Comprehensive Income reporting can mitigate excessive profit management tactics, thereby increasing the reliability of financial information for stakeholders and strengthening corporate governance.